Green Synthesis of a Novel Silver Nanoparticle Conjugated with Thelypteris glandulosolanosa (Raqui-Raqui): Preliminary Characterization and Anticancer Activity - Vera-Nuñez, Lucero Del Carmen (2022)
“In the last decade, the green synthesis of nanoparticles has had a prominent role in scientific research for industrial and biomedical applications. In this current study, silver nitrate (AgNO3 ) was reduced and stabilized with an aqueous extract of Thelypteris glandulosolanosa (Raqui-raqui), forming silver nanoparticles (AgNPs-RR). UV-vis spectrophotometry, dynamic light scattering (DLS), and scanning transmission electron microscopy (STEM) were utilized to analyze the structures of AgNPsRR. The results from this analysis showed a characteristic peak at 420 nm and a mean hydrodynamic size equal to 39.16 nm, while the STEM revealed a size distribution of 6.64–51.00 nm with an average diameter of 31.45 nm. Cellular cytotoxicity assays using MCF-7 (ATCC® HTB-22™, mammary gland breast), A549 (ATCC® CCL-185, lung epithelial carcinoma), and L929 (ATCC® CCL-1, subcutaneous connective tissue of Mus musculus) demonstrated over 42.70% of MCF-7, 59.24% of A549, and 8.80% of L929 cells had cell death after 48 h showing that this nanoparticle is more selective to disrupt neoplastic than non-cancerous cells and may be further developed into an effective strategy for breast and lung cancer treatment. These results demonstrate that the nanoparticle surfaces developed are complex, have lower contact angles, and have excellent scratch and wear resistance.“